The Influence of Peer Pressure and Perceived Benefits on Self-Control among Drug Abusers in Class II A Banceuy Prison, Bandung - Intan Nur Rahmawati; Rifqi Farisan Akbar (International Journal of Marketing & Human Resource Research, 2026)
Drug abuse is a problem related to self-control behavior among correctional inmates. Self-control is an important psychological construct in rehabilitation because it reflects an individual's ability to regulate impulses, respond to social pressures, and make sound behavioral decisions. The purpose of this study was to examine the influence of peer pressure and perceived benefits on self-control among inmates with a history of drug abuse. The study subjects consisted of 50 inmates. Data were collected using peer, perceived benefit, and self-control scales. Data analysis was performed using a discriminant analysis, yielding a discriminant function with a coefficient of 0.037, indicating that peer pressure and perceived benefits contribute 3.7% to self-control. The F test showed that the two independent variables did not have a significant effect on self-control (p > 0.05), peer pressure (p = 0.197), and perceived benefit (p = 0.912). These findings indicate that variations in self-control among correctional facility residents are more strongly influenced by factors other than peer pressure and perceived benefits, thereby necessitating a review of additional psychological and contextual variables in further research.